Nitrogen deposition and climate change have increased vascular plant species richness and altered the composition of grazed subalpine grasslands. (27th February 2017) - Boutin, Marion; Corcket, Emmanuel; Alard, Didier; Villar, Luis; Jiménez, Juan‐José; Blaix, Cian; Lemaire, Cédric; Corriol, Gilles; Lamaze, Thierry; Pornon, André
Summary: Atmospheric nitrogen (N) deposition and climate warming are two major components of global change that drive species richness and composition in plant communities. However, their combined effects have been insufficiently investigated across large spatial and temporal scales particularly in high‐elevation, nutrient‐limited ecosystems. We examine whether and how N deposition and climate warming have altered the plant richness and the composition of subalpine semi‐natural, extensively grazed grasslands of the Pyrenees, using two complementary approaches: (i) analysis of 553 relevés to explore vegetation changes across large ecological gradients including temperature and N deposition (spatial approach) and (ii) a re‐sampling of a subset of 40 sites among the 553 sites to assess temporal changes over the past decades (temporal approach). Both approaches showed that the vascular plant species richness increased when temperature and cumulative N deposition increase, shifting the species composition towards more thermophilic and eutrophic communities. Synthesis . We hypothesize that the release from abiotic constraints (milder temperature and higher nitrogen availability) due to global changes and long‐standing extensive grazing counteracting the negative effects of nitrogen deposition have been responsible for the diversity and compositional changes of plant communities over the last decades in the Pyrenees. Thus, in contrast with other grasslands, high‐elevation grazed grasslands may increase in species diversity with nitrogen deposition under climate warming. Abstract : We hypothesize that the release from abiotic constraints (milder temperature and higher nitrogen availability) due to global changes and long‐standing extensive grazing counteracting the negative effects of nitrogen deposition have been responsible for the diversity and compositional changes of plant communities over the last decades in the Pyrenees. Thus, in contrast with other grasslands, high‐elevation grazed grasslands may increase in species diversity with nitrogen deposition under climate warming.